The antecedents and consequences of value co-creation behaviors in a hotel setting: a two-country study - Roy, Sanjit K.; Balaji, M. S.; Soutar, Geoffrey; Jiang, Yangyang (SAGE Publications Inc., 2019)
This study examines the antecedents and consequences of value co-creation behavior in a hospitality context. An online questionnaire with samples of hotel patrons in the United States and Australia was used to obtain data and partial least square modeling was used in the analysis. The results suggest patron fairness perception enhances trust and identification with a hotel, which encourage engagement in the value co-creation behavior. Furthermore, this behavior enhances patron well-being and respect for the hotel. The study contributes to the literature by suggesting a value co-creation behavior model in the hospitality context and empirically examining the antecedents and consequences of this behavior. The results have important implications for managers designing service encounters that can encourage hotel patrons to engage in the value co-creation behavior.